Urban Sustainability, Agglomeration Forces and the Technological Deus ex Machina - Erik Verhoef; Peter Nijkamp; Joe Daniel (Tinbergen Institute, 2001)
This paper aims to analyze and depict urban equilibrium from the perspective of acomplex force field between (positive) agglomeration economies and (negative) environmentalexternalities. Based on a simplified representation of a linear urban economy, anarchetypical model based on general equilibrium principles is designed and its propertiesare investigated by using numerical simulations. The model includes a spacious industrial centrein which agglomeration externalities are differentiated over space, and a residential area thatsuffers from pollution which too is differentiated over space. Environmental technology choiceby firms is endogenized. This model is able to generate interesting and sometimescounter-intuitive results for the city under consideration.
Keywords: 330; Stadtökonomik; Regionales Cluster; Agglomerationseffekt; Umweltbelastung; Räumliche Gleichgewichtstheorie; Theorie